Practical manual of clinical obesity - Kushner, Robert F., 1953-; Lawrence, Victor, 1968-; Kumar, Sudhesh; Wiley InterScience (Online service) (Chichester, West Sussex ; Hoboken, NJ : Wiley-Blackwell, 2013)
This accessible guide to obesity and its clinical management provides clear, didactic, clinically focused guidance for all healthcare professionals involved in the treatment and management of patients with obesity, thus acting as a repository of essential practical knowledge. It is an ideal practical guide for registrars and residents in endocrinology and metabolic disease, as well as all other health professionals who regularly manage obese patients, such as specialist obesity and diabetes nurses, dietitians, and general practitioners with an interest in obesity management.
Energy balance and body weight homeostasis -- The genetic basis of obesity -- Adipocyte biology -- Fetal and infant origins of obesity -- Metabolic fuels and obesity -- Practical guide to clinical assessment and treatment planning -- Patterns, risks, and benefits of weight loss -- Dietary management -- Physical activity and exercise -- Behavioral therapy -- Pharmacotherapy -- Surgical treatments -- Diabetes and metabolic diseases -- Obesity and reproductive health -- Gastrointestinal and hepatobiliary disease in obesity -- Respiratory complications of obesity -- Obesity and cardiovascular disease -- Obesity : mental health and social consequences -- Obesity and musculoskeletal disease -- The obese patient in hospital.
Includes bibliographical references and index.
Online resource; title from digital title page (viewed on June 24, 2013).
Print version record.
Keywords: Obesity -- Handbooks, manuals, etc; Obesity; Obesity; Electronic books; Handbooks and manuals